(untitled) (Journal of Hama University, 2020)
This is a phenomenon that take the speech away from the purpose of the phenomena. To the cause of eloquence causes which impresses in thoughts and senses . And try to put the light on the scientists of eloquence explanation to discover the origins of koranic systematize when verses exit from the appearance issue . It carries interpretation and guidance that not refer to during the speech . The issue that dhws attention to the reader and push him to the entrance of the appearance context . To know the exactly meaning that the verses want The pictures of the speech exit varies from the appearance purpose . To which the exit of acquaint in opposition to apparent . And put the tacit in the position of transfiguration and the opposite is correct . And the many kinds of the verbs among past , present and the future . And the style of heed , sage technique etc.